LEGAL PROTECTION OF CIBETUS SERANG BANTEN RESIDENTS AS ENVIRONMENTAL WARRIORS WHO ARE CRIMINALIZED BY CORPORATIONS (ANALYSIS OF DECISION NO.228/Pid.B/2025/PN SRG) - Miafiz Nur Chairani Nasution; Ibrahim Nainggolan (Inspiring Law Journal, 2026)
This study aims to analyze the legal protections available to residents of Cibetus, Serang Regency, Banten, as environmental activists who have been criminalized by corporations, as well as to examine the legal considerations in Judgment No. 228/Pid.B/2025/PN SRG. The issues addressed include the forms of criminalization against residents, the implementation of legal protection under Law No. 32 of 2009 on Environmental Protection and Management, and an analysis of the application of the Anti-Strategic Lawsuit Against Public Participation (Anti-SLAPP) principle in the aforementioned judgment.This study employs a normative legal research method using both a statutory approach and a case-based approach. The data sources include primary legal materials such as statutes and court decisions, as well as secondary legal materials such as books, journals, and relevant legal literature. The data were analyzed qualitatively to arrive at systematic and comprehensive conclusions.The research findings indicate that the actions taken against the residents of Cibetus suggest a potential for the criminalization of public participation in advocating for the right to a good and healthy environment. Normatively, Article 66 of the Environmental Protection and Management Law (UUPPLH) guarantees legal protection to anyone advocating for the right to a healthy environment, ensuring they cannot be prosecuted criminally or sued in civil court. However, in practice, the application of the Anti-SLAPP principle in Judgment No. 228/Pid.B/2025/PN SRG has not yet fully reflected optimal protection for environmental advocates. Therefore, it is necessary to strengthen the implementation of legal protection norms and ensure consistency among law enforcement officials in guaranteeing the public’s right to participate in environmental management and protection.